The Relationship of the Andragogical Approach to the Level of Learning Motivation of Citizens Learning Package C Program in PKBM Mentari Wagir Subdistrict, Malang District - Permatasari, Shinta Dwi; Dayati, Umi; Listyaningrum, R Anggia (Universitas Negeri Malang, 2024)
Research This aim analyze connection between approach andragogy and levels motivation Package C program participants at PKBM Mentari, Wagir, Malang. Approach researched andragogy focuses on relevance material, involvement active participants, flexibility time learning, and recognition to experience life participants who can increase motivation Study. Motivation evaluated learning covers internal and external factors. Use method quantitative, data is collected through distributed questionnaires to Package C program participants at PKBM Mentari. Questionnaire This measure experience participant with approach andragogy facilitator and level motivation Study they. Data analysis used the Spearman rank correlation test. Research result show exists connection significant positive between approach andragogy and motivation Study. Findings This expected can give outlook about implementation approach andragogy and its effects to motivation Study Package C program participants at PKBM Mentari. This study can contribute to development method more learning effective for adult education, esp in the equality program. Additionally, research This can become base for studies more carry on about influencing factors motivation adult learning in the PKBM environment